A FORMAÇÃO DO LEITOR E O ENSINO DA LITERATURA - Ricardo Magalhães Bulhões (Universidade do Oeste Paulista, 2005)
This is a report of an ongoing research. Theoretically its basic objective is to suggest certain connections between literature and education, verifying to what extension the traditional ways of expression are affected by the transforming power of language, also observing mechanical methodological alternatives, wick promote the lack of interest for literature texts.